2016
DOI: 10.1590/1806-9061-2016-0270
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Replacement of Soybean Meal with Pea as Dietary Protein Source on the Serum Protein Fractions of Broilers

Abstract: The aim of this study was to determine the effects of the replacement of different levels of protein derived from soybean meal with that from peas in broiler diets on serum protein fractions. A corn-soybean meal basal diet was formulated as the control diet (Control=C) (NRC, 1994), and then pea was added to the control diet to replace 20% (P20) or 40% (P40) of the crude protein of the control diet. The diets were randomly fed to 12 pens per treatment, each housing five birds, for 42 days. Blood samples were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
1
8
0
2
Order By: Relevance
“…Serum albumin and total proteins, responsible of osmotic pressure balance and transport of substances in the blood, resulted significantly higher in the group fed the Pea diet. Such results are in agreement with Bingol et al (2016) who found higher blood total protein concentration in broilers fed a diet with 20% of pea replacing soybean. It may be assumed that pea aminoacidic composition influenced total protein concentration.…”
Section: Discussionsupporting
confidence: 93%
“…Serum albumin and total proteins, responsible of osmotic pressure balance and transport of substances in the blood, resulted significantly higher in the group fed the Pea diet. Such results are in agreement with Bingol et al (2016) who found higher blood total protein concentration in broilers fed a diet with 20% of pea replacing soybean. It may be assumed that pea aminoacidic composition influenced total protein concentration.…”
Section: Discussionsupporting
confidence: 93%
“…The reduction of CP with supplemental crystalline amino acids alleviates the demand for SBM, yet alternative protein sources will also be important for meeting the anticipated increase in demand for protein in animal and poultry feed. Alternatives for SBM in broiler diets have been investigated, including traditional and novel options such as canola meal, blood meal, meat and bone meal, fish meal, peameal, sunflower meal, insect meal, and numerous algae species (8)(9)(10)(11)(12). Many of the trials involving algae in broiler feed have focused on growth performance or meat quality with limited mechanistic explanations for their beneficial effects.…”
Section: Introductionmentioning
confidence: 99%
“…In poultry, the digestibility of pea protein is quite high reaching the 84% threshold (Mihailovic et al 2005), and the addition of peameal in diets for broilers can improve the carcase quality and the lipid profile, without adverse effects on growth performance (Laudadio and Tufarelli 2010). The replacement of 20% of SBM protein with pea protein increased the beta and gamma globulin contents of boiler blood suggesting potentially interesting effects on the birds' immunity (Bingol et al 2016). The digestibility of field pea and other pulses (Desi and Kabuli chickpeas, faba bean and white lupin) as alternative protein sources have been tested in rainbow trout and Nile tilapia by Magalhães et al (2018).…”
Section: Composition and Nutritive Value Of Pulses And Other Plant Prmentioning
confidence: 99%